2011
DOI: 10.4103/1658-354x.76484
|View full text |Cite
|
Sign up to set email alerts
|

Palonosetron: A novel approach to control postoperative nausea and vomiting in day care surgery

Abstract: Background:Postoperative nausea and vomiting (PONV) is one of the complications which hamper the successful implementation of day care surgical procedure in spite of the availability of so many antiemetic drugs and regimens for its prevention. The aim was to compare the prophylactic effects of intravenously (IV) administered ondansetron and palonosetron on PONV prevention in patients undergoing laparoscopic gynecological surgery under general anesthesia.Methods:A prospective double-blind study comprised of 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 35 publications
(47 reference statements)
0
40
0
1
Order By: Relevance
“…In our study, incidence of headache was 9.7% in Ondansetron group and 2.4% in Palonosetron group which was found to be statistically significant (p=0.0331) as shown in Table B6 and comparable to study conducted by Bazwa SS et al (2011). 11 , in which 20% of the patients in Ondansetron group experienced significant post-op headache as compared to 6.67% in Palonosetron group. Unlikely, there was no significant difference in side effects observed in Park SK, Cho EJ (2011).…”
Section: Statistical Toolsmentioning
confidence: 89%
See 1 more Smart Citation
“…In our study, incidence of headache was 9.7% in Ondansetron group and 2.4% in Palonosetron group which was found to be statistically significant (p=0.0331) as shown in Table B6 and comparable to study conducted by Bazwa SS et al (2011). 11 , in which 20% of the patients in Ondansetron group experienced significant post-op headache as compared to 6.67% in Palonosetron group. Unlikely, there was no significant difference in side effects observed in Park SK, Cho EJ (2011).…”
Section: Statistical Toolsmentioning
confidence: 89%
“…Overall incidence of vomiting in our study was 21.8% in Group O and 4% in Group P with p value of 0.0001 as shown in Table B5, Figure B5 which was statistically significant and comparable to results concluded by Bajwa SS (2011). 11 Park SK, Cho EJ (2011). 9 and Moon YE, Joo J, Kim JE, Lee Y (2012).…”
Section: Statistical Toolsmentioning
confidence: 99%
“…We then retrieved the full texts of the remaining 16 citations and excluded seven of these citations because five among them had no intended interventions and two had no outcomes of interest. Altogether, nine studies [25][26][27][28][29][30][31][32][33] fulfilled the criteria for systematic review and meta-analysis. The study selection processes are shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…In 2008, the FDA approved a single intravenous dose of palonosetron for PONV prophylaxis for up to 24 hours based on the results of two earlier dose-ranging studies. 48,49 Subsequently, most studies [25][26][27][28][29][30][31][32][33] chose palonosetron 0.075 mg as the dose to administer in their trials, which makes it difficult to re-evaluate the optimal dose of palonosetron.…”
Section: Early Povmentioning
confidence: 99%
See 1 more Smart Citation